The Relationship Between Sustainable Leadership and Human Resource Management Practices in Educational Institutions in the Kingdom of Saudi Arabia - Arous, Jamel Ali; ElRabbat, Samar Ahmed; ElAwad, Islah Hassan; Hamdi , Rabeb El; Alruwaili, Roaa Taysir (Journal of Ecohumanism, 2025)
The aim of the study to explore the link between sustainable leadership and HRM practices on organizational performance in educational institutions in the Kingdom of Saudi Arabia, with the mediator role of organizational innovation. Sustainability is now a top priority for educational institutions; therefore, it is crucial to know how leadership practices affect HR management and, therefore, the organization’s performance. The research sample consisted of 256 educational leaders from Saudi schools (Directors, Vice Directors, supervisors, and counselors). The data were analyzed using the JASP statistical program. The results showed that there was a positive relationship between sustainable leadership and HRM practices as it is revealed in organizational performance and the need for sustainability-oriented leadership to enhance effective organizational performance. Furthermore, human resource management practices were found to be positively related to organizational performance thus supporting their role in the attainment of organizational goals. Organizational innovation was found to be an important mediator of the relationship between sustainable leadership and human resource management practices. These results support the notion that sustainable leadership is beneficial in improving human resource management practices by means of organizational innovation in the educational contexts of the Kingdom of Saudi Arabia. Lastly, the study provides practical implications for policy makers and educational leaders to implement sustainable leadership strategies and improve human resource management, which in turn will help the long term success of educational institutions in the Kingdom of Saudi Arabia.